2019
DOI: 10.3389/fimmu.2019.00067
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate Attenuates Lung Inflammation by Negatively Modulating Th9 Cells

Abstract: Th9 cells orchestrate allergic lung inflammation by promoting recruitment and activation of eosinophils and mast cells, and by stimulating epithelial mucus production, which is known to be mainly dependent on IL-9. These cells share developmental pathways with induced regulatory T cells that may determine the generation of one over the other subset. In fact, the FOXP3 transcription factor has been shown to bind il9 locus and repress IL-9 production. The microbiota-derived short-chain fatty acids (SCFAs) butyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 50 publications
0
54
0
1
Order By: Relevance
“…Butyrate-treated mice show lower frequencies of Th9 cells in the lungs, while no difference is observed for Th2 cells (31). Moreover, adoptive transfer of Th9 or IL-9 administration could revert the protective effect of butyrate, indicating that the mechanisms are partially related to this Th subclass (31). Lastly, while the link between obesity and non-allergic bronchial hyperresponsiveness is widely accepted, a high-fat diet has little effect in modulating Tregs responses by an impairment of DCs activation in OVA-induced AAS (33).…”
Section: Diet Modulation Of T Cell Response Is Only Partially Drivenmentioning
confidence: 78%
See 2 more Smart Citations
“…Butyrate-treated mice show lower frequencies of Th9 cells in the lungs, while no difference is observed for Th2 cells (31). Moreover, adoptive transfer of Th9 or IL-9 administration could revert the protective effect of butyrate, indicating that the mechanisms are partially related to this Th subclass (31). Lastly, while the link between obesity and non-allergic bronchial hyperresponsiveness is widely accepted, a high-fat diet has little effect in modulating Tregs responses by an impairment of DCs activation in OVA-induced AAS (33).…”
Section: Diet Modulation Of T Cell Response Is Only Partially Drivenmentioning
confidence: 78%
“…Since Tregs are potent inhibitors of Th9 (32), their capacity to reduce IL-9 expression and Th9 differentiation was assessed. Butyrate-treated mice show lower frequencies of Th9 cells in the lungs, while no difference is observed for Th2 cells (31). Moreover, adoptive transfer of Th9 or IL-9 administration could revert the protective effect of butyrate, indicating that the mechanisms are partially related to this Th subclass (31).…”
Section: Diet Modulation Of T Cell Response Is Only Partially Drivenmentioning
confidence: 90%
See 1 more Smart Citation
“…First of all, recent murine studies showed that butyrate, one of the microbiota‐derived SCFAs, suppressed Th9 cell responses in a lung inflammation setting. Specifically, butyrate reduced the frequency of Th9 cells in the lung and subsequently reduced eosinophil infiltration and lung inflammation …”
Section: Association Between the Microbiota Dietary Compounds And Thmentioning
confidence: 99%
“…Specifically, butyrate reduced the frequency of Th9 cells in the lung and subsequently reduced eosinophil infiltration and lung inflammation. 56 In addition, antagonizing effects of retinoic acid (RA), a dietary metabolite of vitamin A which is synthesized by mucosal dendritic cells (DCs), were described. 57 RA showed to impact the transcriptome of Th9 cells while not affecting other T helper subtypes to the same extent.…”
Section: Albicans • Il-9 Producing Cells (Including T Cells) and Mamentioning
confidence: 99%